1998
DOI: 10.1042/bj3320237
|View full text |Cite
|
Sign up to set email alerts
|

The iron ligand sphere geometry of mammalian 15-lipoxygenases

Abstract: We investigated the geometry of the iron ligand sphere of the native rabbit 15-lipoxygenase (15-LOX) by X-ray absorption spectroscopy using synchrotron radiation. The soybean LOX-1 was used as a reference compound because its iron ligand sphere is well characterized. For structural information the X-ray absorption spectra were evaluated using the Excurve Program (CCLRC Daresbury Laboratory, Warrington, U.K.). From the positions of the absorption edges and from the intensities of the 1s-3d pre-edge transition p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
17
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 31 publications
4
17
1
Order By: Relevance
“…Inhibition of both plant and mammalian 15-LOX-dependent lipid oxidation by high concentrations of nitric oxide ( ⅐ NO) was ascribed to formation of an enzyme-nitrosyl complex (25)(26)(27). Nitric oxide can form a nitrosyl complex with the active site of 15-LOX, a single six-coordinate ferrous iron liganded to nitrogen and/or oxygen atoms (28), that is detectable by electron paramagnetic resonance spectroscopy (EPR). The spectrum of the soybean 15-LOX Fe 2ϩ -⅐ NO complex contains two species, the first attributed to either high spin ferric iron, formed by transfer of an electron from Fe 2ϩ to ⅐ NO, or an S ϭ 3/2 system resulting from antiferromagnetic coupling of axial (D Ͼ E) high spin ferrous iron to ⅐ NO (29 -31).…”
mentioning
confidence: 99%
“…Inhibition of both plant and mammalian 15-LOX-dependent lipid oxidation by high concentrations of nitric oxide ( ⅐ NO) was ascribed to formation of an enzyme-nitrosyl complex (25)(26)(27). Nitric oxide can form a nitrosyl complex with the active site of 15-LOX, a single six-coordinate ferrous iron liganded to nitrogen and/or oxygen atoms (28), that is detectable by electron paramagnetic resonance spectroscopy (EPR). The spectrum of the soybean 15-LOX Fe 2ϩ -⅐ NO complex contains two species, the first attributed to either high spin ferric iron, formed by transfer of an electron from Fe 2ϩ to ⅐ NO, or an S ϭ 3/2 system resulting from antiferromagnetic coupling of axial (D Ͼ E) high spin ferrous iron to ⅐ NO (29 -31).…”
mentioning
confidence: 99%
“…[28,29] It constitutes a regular octahedron that is slightly distorted. Four histidine residues (His361, His366, His541, and His545) and the C-terminal isoleucine residue (Ile663) have been identified as protein iron ligands and the sixth ligand position appears to be occupied by a water molecule or a hydroxy ion.…”
Section: Structure Modelingmentioning
confidence: 99%
“…The various analyses are consistent with a six-coordinate iron, bound by three or four nitrogen ligands (imidazole) and one or two oxygen ligands in an octahedral symmetry. It is evident from x-ray analysis that not all six bonds to the central iron atom are from the protein and that there are possible coordination sites that are either unoccupied or coordinated by weak ligands (12)(13)(14)(15)(16). Such sites may represent potential sites of coordination by metal chelators (8).…”
mentioning
confidence: 99%
“…Of significance is a 37-amino acid sequence containing 5 histidines that are conserved in all cloned lipoxygenases (10,11). It has been suggested that this region may be involved in iron coordination (10,11,15,16). 5-LO contains 1 mol of iron/mol of enzyme (10,11).…”
mentioning
confidence: 99%
See 1 more Smart Citation